(untitled) (Tabanque. Revista Pedagógica, 2024)
This article examines the advantages and disadvantages of integrating Artificial Intelligence (AI) into education, highlighting how personalized learning, access to educational resources, instant feedback, and administrative task automation are key benefits offered by AI. However, ethical concerns regarding data privacy and potential job displacement are raised. In this context, the importance of addressing these challenges to maximize the benefits of AI in education while mitigating potential risks is emphasized.